Why Not Market Yourself? - Barbara MacAlpine (Issues in Science and Technology Librarianship, 2006)
Reflects on ways to market an academic librarian's services. Advantages of serving on campus committees; Suggestions for bringing a cultural or social program to the school; Details of getting involved in solving a problem on campus.